Evaluation of the Therapeutic Effectiveness of Combined Action Antiallergic Drugs in Monotherapy of Allergic Conjunctivitis - N. G. Zumbulidze; V. M. Khokkanen; I. B. Litvin (Oftalʹmologiâ, 2020)
According to statistical studies in recent decades, there has been an increase of allergic diseases in most countries of the world. Predisposing factors are the deterioration of the environmental situation, the total “chemicalization” of life and the forced use of drugs. Twenty years ago, the World Health Organization called the new century “the century of allergies” and the disease itself as an “epidemic”. As time has shown, these forecasts have come true: from 2001 to 2010, the number of allergic people in the world increased by 20 % and many of these patients suffer from ophthalmic manifestations of the pathology: the eyes are involved in the process in almost every second case. This is due to the fact that the eyes are directly exposed to the environment and a variety of external allergens. The most common disease of an eye-allergic nature is allergic conjunctivitis: approximately 15 % of the total population of economically developed countries suffer from it. Allergic blepharitis, eyelid dermatitis, keratitis, iritis, uveitis, retinitis and optic neuritis are much less common. The following manifestations are typical for allergic conjunctivitis: burning, lacrimation, pruritus, hyperemia of the eyelids and conjunctiva, photophobia. In the case of a transition to a chronic form, pronounced tissue changes are observed. Therefore, timely diagnosis and effective treatment certainly have a positive effect on the quality of life of the patient and the course of the disease. The treatment of patients with allergic conjunctivitis, first of all, consists in the maximum possible restriction of contact with the allergen. During desensitizing therapy, local and general drugs are used. Numerous studies have proven the advantage of targeted and effective antiallergic local therapy compared with systemic exposure. Currently used local ophthalmic antiallergic drugs belonging to various groups. The tactics of their use is determined by the acuity, severity and etiology of the process. When choosing a drug, in some cases, you should focus on the presence of substances that provide a double mechanism of action: a pronounced antihistamine activity in combination with the stabilization properties of mast cells, which has a quick and long therapeutic effect. This study evaluated efficacy of Vizallergol (olopatadin 0.2 %) application in cases of allergic conjunctivitis in 239 patients was evaluated. The medication arrested the symptoms of allergic conjunctivitis in 89 % of patients, at that the mean period of treatment made 10.7 ± 0.3 days. In the treatment of allergic conjunctivitis, the therapeutic efficacy of Vizallergol 0.2 % was comparable to opatanol 0.1 % and was found to be more comfortable for most patients due to the convenience of a single use.